Oud neg.nr. 74935-74942. 'Foto's van onderwijs aan buitenlandse kinderen, Boumanschool, Amsterdam' - Haas, Joh. de
Oud neg.nr. 74935-74942. 'Foto's van onderwijs aan buitenlandse kinderen, Boumanschool, Amsterdam'.